2023
DOI: 10.3390/cardiogenetics13020007
|View full text |Cite
|
Sign up to set email alerts
|

Brugada Syndrome within Asian Populations: State-of-the-Art Review

Abstract: Brugada syndrome (BrS) is an inherited cardiac channelopathy with variable expressivity that can lead to sudden cardiac arrest (SCA). Studies worldwide suggest that BrS and Brugada pattern (BrP) have low prevalences in general. However, studies also note that BrS is most prevalent among certain Asian populations. Among the different global regions, the highest prevalence is believed to be in Southeast Asia, followed by the Middle East, South Asia, East Asia, Europe, and North America. It is not only important … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Also, each ethnic group with LQTS is associated with a specific more prevalent genetic variant. For example, genetic variants in the SCN5A gene of individuals with LQTS are more prevalent in African American people, increasing the risk of sudden death ( Killen et al, 2010 ), while Brugada syndrome (BrS) associated with SCN5A variants have been reported more frequently in Caucasians and Asians individuals ( Milman et al, 2019 ; Chen et al, 2020 ; Nakano and Shimizu, 2022 ), although BrS phenotype is more prevalent in East and Southeast Asia ( Nakano and Shimizu, 2022 ; Khawaja et al, 2023 ). Instead, genetic variants in the KCNQ1 and KCNH2 genes have been described to be more prevalent in people with European and Japanese ancestry ( Lahrouchi et al, 2020 ; Winbo et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Also, each ethnic group with LQTS is associated with a specific more prevalent genetic variant. For example, genetic variants in the SCN5A gene of individuals with LQTS are more prevalent in African American people, increasing the risk of sudden death ( Killen et al, 2010 ), while Brugada syndrome (BrS) associated with SCN5A variants have been reported more frequently in Caucasians and Asians individuals ( Milman et al, 2019 ; Chen et al, 2020 ; Nakano and Shimizu, 2022 ), although BrS phenotype is more prevalent in East and Southeast Asia ( Nakano and Shimizu, 2022 ; Khawaja et al, 2023 ). Instead, genetic variants in the KCNQ1 and KCNH2 genes have been described to be more prevalent in people with European and Japanese ancestry ( Lahrouchi et al, 2020 ; Winbo et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Arrhythmic manifestations and cardiac arrest in BrS tend to occur in men and populations in Southeast Asian countries. (1,2) Clinical manifestations of BrS can vary from mild discomfort in the form of syncope to sudden death, mostly caused by malignant arrhythmias. It is an autosomal dominant arrhythmia characterized by ST elevation and negative T waves in right heart electrocardiography (ECG) leads without structural cardiac abnormalities, which occur because of mutations in the cardiac sodium gene SCN5A resulting in loss of cardiac sodium channel function, decreased sodium in ux, and depolarization phase shortening of the action potential, which is also associated with sudden cardiac death (3).…”
Section: Introductionmentioning
confidence: 99%
“…It is an autosomal dominant arrhythmia characterized by ST elevation and negative T waves in right heart electrocardiography (ECG) leads without structural cardiac abnormalities, which occur because of mutations in the cardiac sodium gene SCN5A resulting in loss of cardiac sodium channel function, decreased sodium in ux, and depolarization phase shortening of the action potential, which is also associated with sudden cardiac death (3). BrS is endemic in Southeast Asian and East Asian countries (2). This may be due to poor reporting or diagnosis resulting from facility limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Also, each ethnic group with LQTS is associated with a specific more prevalent genetic variant. For example, genetic variants in the SCN5A gene of individuals with LQTS are more prevalent in African American people, increasing the risk of sudden death (Killen et al, 2010), while Brugada syndrome (BrS) associated with SCN5A variants have been reported more frequently in Caucasians and Asians individuals (Milman et al, 2019;Chen et al, 2020;Nakano and Shimizu, 2022), although BrS phenotype is more prevalent in East and Southeast Asia (Nakano and Shimizu, 2022;Khawaja et al, 2023). Instead, genetic variants in the KCNQ1 and KCNH2 genes have been described to be more prevalent in people with European and Japanese ancestry (Lahrouchi et al, 2020;Winbo et al, 2020).…”
Section: Diagnostic Assessmentmentioning
confidence: 99%